Three-dimensional conformal radiation therapy for the osteoarthritis of knee joint: the radiobiological background, dose distribution analysis - М. V. Маkаrоvа; M. Yu. Vаlkov; D. Yu. Tretjakov (Исследования и практика в медицине)
Osteoarthritis (OA) is the most frequent rheumatological pathology of the joints. Standard medical treatment does not always allow to stop the pain syndrome. The alternative method of pain treatment causes by OA is orthovoltage X-ray therapy (OVRT). It was used from 1970. The maximum dose by OVRT lies on the skin surface. Based on the modern methods of diagnosis, choosing the appropriate radiation energy, it is possible to reduce the amount of irradiation of the knee joint.The purpose. Is to present the technique of radiation planning in patients with gonarthritis and compare it with OVRT by dosimetry criteria.Materials and methods. Comparison of dose distribution plans of the orthovoltage beam was carried out according to the two-dimensional axial plan in the area of the isocenter for the energy of 200 kV from two tangential fields and a megavoltage energy beam of 6 MeV for a three-dimensional conformal radiation therapy using 3-and 6-fields isocentric irradiation techniques. To describe amounts of radiation were applied to the CTV (clinical target volume) and PTV (planning target volume). To estimate the volume distribution of the dose, bones forming the knee joint were contoured separately. The indent on the PTV was 3 mm.Results. The application of the 6-fields technique allows achieving 95% dose distribution at 93% of the volume, and 90% of the planned dose of 45 SGR covers 97% of the PTV. The average dose on the skin and the neurovascular bundle are of 150 and 240 cGy, respectively. The average radiation dose per course in critical anatomical areas is 280 cGy and 150 cGy. It can be considered that the target coverage for the compared methods is similar as for OVRT, and for 3D conformal radiation therapy plans for dose distribution of the orthogonal beam in the axial plane in comparison with dose distributions for conformal radiation techniques.Conclusion. The technique of three-dimensional conformal radiation therapy of the knee joint in OA with progressive pain syndrome can potentially lead to an increase in the analgesic eﬀect due to greater coverage with a dose of bone elements of the joint, which are a potential source of pain. Three-dimensional conformal radiotherapy megavoltage beam allows reducing the radiation load on the skin in 2.5 times, which can reduce the frequency of delayed adverse eﬀects.